A Discussion on the Factors Affecting Organizations and Management Performance: A Lesson Learned for Business Students - Channarika, Kan; Mardy, Serey (International Journal of Management and Business Intelligence, 2024)
All managers these days search for the variables that impact individual or organizational outcomes such as productivity and performance. Organizational culture is among these variables. A growing number of people recognize organizational culture as a resource that businesses may leverage to boost productivity. Corporate culture is a crucial idea, yet it can be difficult to articulate in precise terms. In order to better understand how the term "culture" was appropriated by industrial organization academics to refer to organizational culture, this paper will first examine how the term originated in anthropology. A survey on organizational culture's function in organizations was conducted as part of the research. Long-standing beliefs and values inside an organization, as well as staff beliefs and the importance of their work that they anticipate will shape their attitudes and behaviors, are all considered aspects of its organizational culture. To achieve the organization's goal, administrators typically modify their leadership style, which may have an impact on how satisfied workers are with their jobs. Knowing how company culture, leadership style, and employee job satisfaction relate to one another is therefore crucial. Tales, customs, tangible symbols, and language can all be used to impart knowledge. Lastly, job happiness, commitment, empowerment, productivity, performance, and even customer satisfaction may all be impacted.